Answer:
x=-6
Step-by-step explanation:
Let x be the number
3x = x^2 -54
Subtract 3x
3x-3x = x^2 -3x-54
0 = x^2 -3x-54
Factor
What 2 numbers multiply to -54 and add to -3
-9*6 = -54
-9+6 = -3
0=(x-9) (x+6)
Using the zero product property
x-9=0 x+6=0
x=9 x=-6
The questions asks for the negative solution
x=-6
Answer:
<em>s = 5.4</em>
Step-by-step explanation:
2^2 + 5^2 = s^2
s^2 = 4 + 25
s^2 = 29
s = sqrt(29)
s = 5.4
Answer:
Exact Form:
x
=
1
2
Decimal Form:
x
=
0.5
Step-by-step explanation:
80
8 x 10
2 x 4 x 5 x 2
2 x 2 x 2 x 2 x 5 <===
Answer:
P=4
Step-by-step explanation: